Preparation and characterization of low molecular weight chitosan with different degrees of deacetylation by the acid hydrolysis method - Al-Jbour, Nawzat D.; M. D. H., Beg; Jolius, Gimbun; A. K. M., Moshiul Alam (Innovare Academics Sciences Pvt. Ltd, 2021)
Objective: The objective of this research is to prepare Low Molecular Weight Chitosan (LMWC) by the acid hydrolysis method, using dilute hydrochloric acid (2M). LMWC has superior properties compared to the High Molecular Weight Chitosan (HMWC), especially in terms of water solubility, antibacterial and antifungal properties. These could open new potential applications for LMWC in sectors such as the cosmetics, food, and pharmaceutical industries. Methods: In this work, the acid hydrolysis method was used to produce LMWC with different molecular weights starting from 500 kDa and 93% degree of deacetylations (DDA). The molecular weights of the produced grades were determined by applying Mark-Houwink equation while the %DDA was determined and verified by the use of the 1st derivative UV method and1HNMR method, respectively. The depolymerization reactions were carried out with different time intervals to produce totally deacetylated LMWC of 30 kDa, 15 kDa, and 7.5 kDa. The LMWC was characterized by FTIR, XRD, and DSC to evaluate the functionality, microstructure and thermal properties. Results: The FTIR spectra revealed that there is no significant difference in the main skeletal structure of the LMWC and HMWC. On the other hand, the XRD and DSC results showed that the LMWC of different molecular weights and degrees of deacetylation are of semi-crystalline structure, similar to the HMWC. Conclusion: The obtained results showed that the used acid hydrolysis procedure can produce LMWC grades of desired specifications, yields, and quality which are suitable for use in different applications.